Identification of the main flavonoids of Abelmoschus manihot (L.) medik and their metabolites in the treatment of diabetic nephropathy - Diao, Zhipeng; Yu, Hongmei; Wu, Yapeng; Sun, Yuanbo; Tang, Haitao; Wang, Mei; Li, Nan; Ge, Haitao; Sun, Jianguo; Gu, Harvest F. (Frontiers in Pharmacology, 2024)
Introduction: Huangkui capsule (HKC) is made from the ethanol extract of Abelmoschus manihot (L.) Medik [Malvaceae; abelmoschi corolla] and received approval from the China Food and Drug Administration (Z19990040) in 1999. Currently, HKC is used for treatment of the patients with diabetic nephropathy (DN) in China. The bioactive chemical constituents in HKC are total flavonoids of A. manihot (L.) Medik (TFA). The present study aims to identify the primary flavonoid metabolites in HKC and TFA and their metabolism fates in db/db mice, the animal model for the study of type 2 diabetes and DN. Methods: HKC (0.84 g/kg/d) and TFA (0.076 g/kg/d) or vehicle were respectively administered daily via oral gavage in db/db mice for 4 weeks. The metabolism fate of the main metabolites of HKC in serum, liver, kidney, heart, jejunum, colon, jejunal contents, colonic contents, and urine of db/db mice were analyzed with a comprehensive metabolite identification strategy. Results and Discussion: In db/db mice administered with HKC and TFA, 7 flavonoid prototypes and 38 metabolites were identified. The related metabolic pathways at Phases I and II reactions included dehydroxylation, deglycosylation, hydrogenation, methylation, glucuronidation, sulphation, and corresponding recombined reactions. Quercetin, isorhamnetin, quercetin sulphate, quercetin monoglucuronide, and isorhamnetin monoglucuronide presented a high exposure in the serum and kidney of db/db mice. Thereby, the present study provides a pharmacodynamic substance basis for better understanding the mechanism of A. manihot (L.) Medik for medication of DN.